Exploring future changes in smallholder farming systems by linking socio-economic scenarios with regional and household models - Herrero, Mario; Thornton, Philip K.; Bernués, A.; Baltenweck, Isabelle; Vervoort, Joost M.; Steeg, Jeannette van de; Makokha, S.; Wijk, Mark T. van; Karanja, S.; Rufino, Mariana C.; Staal, Steven J. (Elsevier, 2014)
We explore how smallholder agricultural systems in the Kenyan highlands might intensify and/or diversify in the future under a range of socio-economic scenarios. Data from approximately 3000 households were analyzed and farming systems characterized. Plausible socio-economic scenarios of how Kenya might evolve, and their potential impacts on the agricultural sector, were developed with a range of stakeholders. We study how different types of farming systems might increase or diminish in importance under different scenarios using a land-use model sensitive to prices, opportunity cost of land and labour, and other variables. We then use a household model to determine the types of enterprises in which different types of households might engage under different socio-economic conditions. Trajectories of intensification, diversification, and stagnation for different farming systems are identified. Diversification with cash crops is found to be a key intensification strategy as farm size decreases and labour costs increase. Dairy expansion, while important for some trajectories, is mostly viable when land available is not a constraint, mainly due to the need for planting fodders at the expense of cropland areas. We discuss the results in relation to induced innovation theories of intensification. We outline how the methodology employed could be used for integrating global and regional change assessments with local-level studies on farming options, adaptation to global change, and upscaling of social, environmental and economic impacts of agricultural development investments and interventions.